Formulation and Characterization of Resveratrol-Loaded Nanostructured Lipid Carriers (NLC) with Mesua ferrea Seed Oil as Liquid Lipid - Lahan, Madhuchandra (Sciences of Pharmacy, 2024)
Nanostructured Lipid Carriers (NLCs) are colloidal drug delivery systems composed of both solid and liquid lipids. They enhance drug loading capacity, regulate the release of poorly water-soluble drugs, and are suitable for targeted delivery. Resveratrol, a polyphenol with promising anticancer properties, faces challenges due to its low water solubility, poor bioavailability, and chemical instability, resulting in rapid metabolism and excretion. Therefore, it is crucial to develop a delivery system that safeguards resveratrol during its transit through the body. This study aimed to develop and characterize resveratrol-loaded NLCs using the nano-precipitation method followed by ultrasonication, incorporating Mesua ferrea seed oil as the liquid lipid. The NLCs were evaluated for particle size, morphology (TEM), zeta potential, drug entrapment efficiency, drug loading, and in vitro drug release. The resulting NLCs demonstrated stability and homogeneity, with a particle size of 181.6 ± 12.4 nm, a polydispersity index (PDI) of 0.135 ± 0.09, drug entrapment efficiency of 82.76 ± 12.2%, and drug loading capacity of 42.94 ± 7.5%. They exhibited sustained drug release, achieving 84.56% release within 24 h. These findings suggest that the developed NLCs can effectively enhance the incorporation and controlled release of poorly water-soluble drugs like resveratrol, offering potential advantages over conventional delivery systems.